An Elderly Woman with Complaints of Pain and Hearing Loss, Diagnosed with CMT1A with PMP22 Duplication - Hamada, Masashi; Sakuishi, Kaori; Yamaguchi-Takegami, Nanaka; Toda, Tatsushi; Takegami, Naoki (Internal Medicine, 2024)
Charcot-Marie-Tooth (CMT) disease is a heterogeneous hereditary motor and sensory neuropathy of the peripheral nervous system, with CMT1A in particular being the most common form. We encountered a 76-year-old woman with CMT1A who had a history of pain attacks and hearing loss from a young age, with motor symptoms manifesting late in life. Her pain and hearing loss may have been related to CMT. Our case also raises the possibility that neuropathic pain and hearing loss may precede the classic motor symptoms of CMT1A.